Safety and efficacy of multipotent adult progenitor cells in acute ischaemic stroke (MASTERS): a randomised, double-blind, placebo-controlled, phase 2 trial. Issue 5 (May 2017) - Hess, David C; Wechsler, Lawrence R; Clark, Wayne M; Savitz, Sean I; Ford, Gary A; Chiu, David; Yavagal, Dileep R; Uchino, Ken; Liebeskind, David S; Auchus, Alexander P; Sen, Souvik; Sila, Cathy A; et al.
Summary: Background: Multipotent adult progenitor cells are a bone marrow-derived, allogeneic, cell therapy product that modulates the immune system, and represents a promising therapy for acute stroke. We aimed to identify the highest, well-tolerated, and safest single dose of multipotent adult progenitor cells, and if they were efficacious as a treatment for stroke recovery. Methods: We did a phase 2, randomised, double-blind, placebo-controlled, dose-escalation trial of intravenous multipotent adult progenitor cells in 33 centres in the UK and the USA. We used a computer-generated randomisation sequence and interactive voice and web response system to assign patients aged 18–83 years with moderately severe acute ischaemic stroke and a National Institutes of Health Stroke Scale (NIHSS) score of 8–20 to treatment with intravenous multipotent adult progenitor cells (400 million or 1200 million cells) or placebo between 24 h and 48 h after symptom onset. Patients were ineligible if there was a change in NIHSS of four or more points during at least a 6 h period between screening and randomisation, had brainstem or lacunar infarct, a substantial comorbid disease, an inability to undergo an MRI scan, or had a history of splenectomy. In group 1, patients were enrolled and randomly assigned in a 3:1 ratio to receive 400 million cells or placebo and assessed for safety through 7 days. In group 2, patients were randomly assigned in a 3:1 ratio to receive 1200 million cells or placebo and assessed for safety through the first 7 days. In group 3, patients were enrolled, randomly assigned, and stratified by baseline NIHSS score to receive 1200 million cells or placebo in a 1:1 ratio within 24–48 h. Patients, investigators, and clinicians were masked to treatment assignment. The primary safety outcome was dose-limiting toxicity effects. The primary efficacy endpoint was global stroke recovery, which combines dichotomised results from the modified Rankin scale, change in NIHSS score from baseline, and Barthel index at day 90. Analysis was by intention to treat (ITT) including all patients in groups 2 and 3 who received the investigational agent or placebo. This study is registered withClinicalTrials.gov, numberNCT01436487 . Findings: The study was done between Oct 24, 2011, and Dec 7, 2015. After safety assessments in eight patients in group 1, 129 patients were randomly assigned (67 to receive multipotent adult progenitor cells and 62 to receive placebo) in groups 2 and 3 (1200 million cells). The ITT populations consisted of 65 patients who received multipotent adult progenitor cells and 61 patients who received placebo. There were no dose-limiting toxicity events in either group. There were no infusional or allergic reactions and no difference in treatment-emergent adverse events between the groups (64 [99%] of 65 patients in the multipotent adult progenitor cell group vs 59 [97%] of 61 in the placebo group). There was no difference between the multipotent adult progenitor cell group and placebo groups in global stroke recovery at day 90 (odds ratio 1·08 [95% CI 0·55–2·09], p=0·83). Interpretation: Administration of multipotent adult progenitor cells was safe and well tolerated in patients with acute ischaemic stroke. Although no significant improvement was observed at 90 days in neurological outcomes with multipotent adult progenitor cells treatment, further clinical trials evaluating the efficacy of the intervention in an earlier time window after stroke (<36 h) are planned. Funding: Athersys Inc.